Strike-slip faulting and hydrothermal alteration in a Proterozoic rapakivi batholith: implications for reservoir formation and geothermal exploration in crystalline cratons-Part 1 - Nordbäck, Nicklas; Bischoff, Alan; Carbajal-Martinez, Daniel; Engström, Jon; Nikkilä, Kaisa; Skyttä, Pietari; Nicol, Andrew; Ovaskainen, Nikolas; Burchardt, Steffi (Springer Nature, 2026)
Ancient crystalline basement cratons are traditionally considered challenging geothermal targets due to their low heat flow, limited porosity, and low matrix permeability. However, fractured and hydrothermally altered crystalline basement rocks can exhibit substantial permeability and fluid storage capacity, making them viable unconventional geothermal prospects. This study examines the brittle deformation processes of the Vehmaa Batholith, a Proterozoic rapakivi intrusion emplaced in Southern Finland, and has implications for geothermal exploration in stable cratonic regions. It evaluates the batholith’s potential to host kilometer-scale geothermal reservoirs and offers insights for exploring geothermal resources in crystalline rocks affected by faulting and hydrothermal alteration. Detailed structural mapping, drone photogrammetry, remote sensing, and paleostress analysis reveal two principal ENE–WSW and NNW–SSE strike-slip fault systems transecting the batholith, interpreted to result from distinct Mesoproterozoic tectonic events. These faults generated extensive fracture networks that align with regional lineaments traceable for ~10–25 km, with scaling relationships indicating damage zones ~100–250 m wide. These fracture networks also exhibit high connectivity, with topological relationship values well exceeding the threshold for continuous fluid pathways, and are typically associated with intense hydrothermal alteration, including chloritization, sericitization, and dissolution-related porosity. The spatial association between brittle structures and hydrothermal alteration supports a model where fluid circulation is controlled by post-magmatic faults, which significantly enhance reservoir properties in crystalline rocks. This has direct implications for geothermal exploration in cratonic regions, where such structures may compensate for otherwise poor hydraulic conditions and enhance advective heat flow. Based on structural criteria, we define five major fault-controlled geothermal targets within the Vehmaa Batholith, representing new exploration opportunities in crystalline basement. Our findings provide the first systematic evidence of large-scale fracture connectivity and reservoir development in rapakivi granites and contribute to broader strategies for identifying geothermal resources in stable continental crust.